2013
DOI: 10.1002/dev.21174
|View full text |Cite
|
Sign up to set email alerts
|

Air stepping in response to optic flows that move Toward and Away from the neonate

Abstract: To shed further light on the perceptual regulation of newborn stepping, we compared neonatal air stepping in response to optic flows simulating forward or backward displacement with stepping forward on a surface. Twenty-two 3-day-olds performed four 60 s trials in which they stepped forward on a table (Tactile) or in the air in response to a pattern that moved toward (Toward) or away (Away) from them or was static (Static). Significantly more steps were taken in the Tactile and Toward conditions than the Stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 30 publications
5
61
2
Order By: Relevance
“…No differences in the amount of stepping were seen in the approaching and receding optic flow conditions relative to the static condition, suggesting a lack of responsiveness to optic flow; however, significantly more air stepping was seen in the receding optic flow condition than in the approaching optic flow condition. Curiously, the amount of air stepping in the approaching optic flow condition was the lowest in the three air stepping conditions, just the opposite of what was observed in newborns (Barbu-Roth et al, 2009, 2013), and seemingly inconsistent with recent reports of enhanced tactile stepping frequency and quality in infants as young as two months of age (with and without disabilities) when optic flow is added to the treadmill on which they are stepping (Pantall, Teulier, Smith, Moerchen, & Ulrich, 2011; Pantall, Teulier, & Ulrich, 2012; Teulier, Barbu-Roth, & Anderson, 2014). Barbu-Roth et al (2015) did not have a tenable explanation for the effects of optic flow they observed in their two month-olds.…”
Section: Introductioncontrasting
confidence: 82%
See 1 more Smart Citation
“…No differences in the amount of stepping were seen in the approaching and receding optic flow conditions relative to the static condition, suggesting a lack of responsiveness to optic flow; however, significantly more air stepping was seen in the receding optic flow condition than in the approaching optic flow condition. Curiously, the amount of air stepping in the approaching optic flow condition was the lowest in the three air stepping conditions, just the opposite of what was observed in newborns (Barbu-Roth et al, 2009, 2013), and seemingly inconsistent with recent reports of enhanced tactile stepping frequency and quality in infants as young as two months of age (with and without disabilities) when optic flow is added to the treadmill on which they are stepping (Pantall, Teulier, Smith, Moerchen, & Ulrich, 2011; Pantall, Teulier, & Ulrich, 2012; Teulier, Barbu-Roth, & Anderson, 2014). Barbu-Roth et al (2015) did not have a tenable explanation for the effects of optic flow they observed in their two month-olds.…”
Section: Introductioncontrasting
confidence: 82%
“…Barbu-Roth et al (2015) also examined whether air stepping in their two month-olds was influenced by approaching and receding optic flows, following earlier studies that showed newborns engaged in more air stepping in response to terrestrial optic flows than to a static pattern (Barbu-Roth, Anderson, Desprès, Provasi, Cabrol, & Campos, 2009; Barbu-Roth et al, 2013). Their findings on two month-olds were difficult to interpret.…”
Section: Introductionmentioning
confidence: 99%
“…The research of Thelen and colleagues [30] demonstrated that the disappearing newborn stepping reflex could be evoked when infants were submerged in water, emphasizing the critical role that environment and gravity exert on locomotor behavior, closely resembling differences between the air-stepping and open field paradigm used here to examine locomotor behavior. However, Barbu-Roth and colleagues [40] found that gravitational constraints are not the only influence on newborn stepping in human infants, but in fact, this response could be influenced and manipulated by visual field stimuli. Overall, utilizing basic research, as well as evidence-based pediatric research, allows us to examine and manipulate systems involved with coordination and locomotion [10], influencing approaches to interventions in pediatric populations [39].…”
Section: Discussionmentioning
confidence: 99%
“…Arousal is one factor as an increase in excitability increases the frequency of movements in the newborn. In addition to internal factors, newborns were recently shown to be capable of adapting the frequency of their leg stepping movements to visual stimuli and tactile stimuli (Barbu-Roth et al, 2009, 2013). In summary, human fetuses and newborns are able to produce rhythmical arm and leg movements and to modulate these movements in response to external stimulation.…”
Section: Rhythm Production In Fetuses and Newbornsmentioning
confidence: 99%
“…The primary goal was to determine whether the rhythmic conditions elicited more stepping than the no rhythmic condition and whether one particular rhythmic condition would elicit more bursts of rhythmic stepping. A secondary goal was to determine whether steps would be synchronized with the external rhythm even though stepping, in contrast to sucking, is highly variable at this age (Barbu-Roth et al, 2009, 2013). Air stepping was chosen for the experimental conditions to determine whether stepping could be induced or facilitated by the audio–visual rhythmic stimuli alone, i.e., in the absence of tactile stimulation.…”
Section: Sensorimotor Synchronization In Neonatesmentioning
confidence: 99%